Development of methodological training of future teachers based on the integration of pedagogical and information technologies - Toshboltaev Fahriddin (Genius Journals, 2022)
This article examines the content, legislative framework and current state of pedagogical and information technology integration in improving the methodological training of future teachers and promoting a potential educator through this
Keywords: modern education; pedagogical opportunities; integration